2013
DOI: 10.4184/asj.2013.7.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Diagnosis of Cauda Eqina Syndrome with Perineural Cyst after Combined Spinal-Epidural Anesthesia in Hemodialysis Patient

Abstract: Symptomatic Tarlov (perineural cysts) are uncommon. In the following hemodialysis case, cauda equina syndrome was not detected after combined spinal-epidural anesthesia untilthe patient reported a lack of sensation in the perianal area 14 days postoperatively. She had normal motor function of her extremities. A laminectomy and cyst irrigation was performed. After the operation, her sphincter disturbance subsided gradually and her symptoms had disappeared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…All these symptoms indicated that he should have CES, and the Tarlov cyst must have an effect on his symptoms [4]. Ishiguro et al described CES associated with S2 root cysts in a patient who underwent a prosthetic femoral removal surgery [9]. Finally, the patient underwent S1 to S5 laminectomy to reduce spinal ow blockage due to stenosis and the laminectomy completely eliminated sensation loss and urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…All these symptoms indicated that he should have CES, and the Tarlov cyst must have an effect on his symptoms [4]. Ishiguro et al described CES associated with S2 root cysts in a patient who underwent a prosthetic femoral removal surgery [9]. Finally, the patient underwent S1 to S5 laminectomy to reduce spinal ow blockage due to stenosis and the laminectomy completely eliminated sensation loss and urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Ishiguro et al described CES associated with S2 root cysts in a patient who underwent a prosthetic femoral removal surgery [ 9 ]. Finally, the patient underwent S1 to S5 laminectomy to reduce spinal flow blockage due to stenosis and the laminectomy completely eliminated sensation loss and urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%